Acquisition – Digitization – Edition: Reflections on the Premodern "Policey" Corpus - Wüst, Wolfgang (Advances in Social Sciences Research Journal, 2022)
The rapid progress in the digitization of early modern sources on an international level in recent decades has fundamentally improved the conditions for historical research. Whereas expensive and time-consuming archival and library studies used to limit the scope of some research projects, long-term editorial projects can now increasingly be tackled from the comfort of one's home. This also applies to the source genre of the “good” Policey. How did it come into being? In the Holy Roman Empire of the German Nation and its regions, institutions and chancelleries, councils and rulers relied on a form of conveying general standards of value that had been drafted in ancient times, was born in the Middle Ages and matured in the early modern period. This legislation was comprehensively designed before the nation-building of the 19th century. As early modern Policey, it was divided into “ordinationes speciales”, “imperiales” and “provinciales”. (1) The first group included dress and luxury ordinances; church and Sunday protection; bans for beer, wine and spirits; hunting, building, market, inn, health, mourning or marriage regulations as well as gambling and lottery bans. (2) The second group consisted of provincial and imperial ordinances, and (3) the third category included territorial, town, market, forest and village ordinances. Edition projects, such as those presented for the University of Erlangen-Nuremberg in southern Germany, are increasingly, but by no means exclusively, based on digitized Policey specifications.